L’hispaniste Antoine de Latour (1808-1881) - Manuel Bruña Cuevas (Cahiers de Civilisation Espagnole Contemporaine)
Latour spent twenty years in Spain; so he ended up being regarded, while remaining French for all to see, almost as a Spaniard. Great scholar, in constant contact with Spanish cultural circles, he was also the secretary of a key figure in Spanish politics of the nineteenth century: the Duke of Montpensier, son of King Louis-Philippe of France and pretender to the Spanish throne. In Spain, Latour was, therefore, a socially well-placed foreigner: he could help the Spanish writers to get the patronage of the Duke as well as publish articles about their work in the Parisian journals.